Genotyping of broiler-originated Campylobacter jejuni and Campylobacter coli isolates using fla-typing and random amplified polymorphic DNA (RAPID) methods (vol 94, pg 203, 2004) - Ertas, HB; Çetinkaya, B; Muz, A; Öngör, H (Elsevier Science Bv, 2004)
[Abstract Not Available]